2001
DOI: 10.1177/0022022101032005004
|View full text |Cite
|
Sign up to set email alerts
|

Action-Control Beliefs and School Experiences of Tanzanian Primary School Students

Abstract: We investigated Tanzanian primary school students’ action-control beliefs about school performance using the revised Control, Agency, and Means-Ends Interview (CAMI) and school experiences controlling for the effects of parental educational level, gender, and age. Five hundred forty-five students (254 boys and 291 girls) in grades 3 through 7 from both urban and rural schools responded to the CAMI questionnaire in Swahili. A structural equation model validated the dimensions of action-control beliefs, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…One of the best ways to learn about this methodology is to study practical applications in your field. Some recent references are the following: ability growth and decline (Raykov, 2000), absenteeism (Geurts, Schaufeli, & Rutte, 1999), academic self concept and achievement (Marsh, Byrne, & Yeung, 1999;Marsh, Hau, & Kong, 2002), acculturation (Gil, Wagner, & Vega, 2000), achievement goals (Elliot & McGregor, 2001), achievement inequality (Carbonaro & Gamoran, 2002), achievement motivation (Barron & Harackiewicz, 2001), achievement tests (Muraishi & Toyoda, 1998), action and coping self-efficacy (Schwarzer, & Renner, 2000), action-control beliefs (Malmberg, Wanner, Sumra, & Little, 2001), ADHD (Rapport, Scanlan, & Denney, 1999), adolescent dating (Wolfe, Scott, Reitzel-Jaffe, Wekerle, Grasley, & Straatman, 2001), affect (Remington, Fabrigar, & Visser, 2000), affect and alcohol problems (McCreary & Sadava, 2000), affirmative action (Iyer, Leach, & Crosby, 2003;Federico & Sidanius, 2002), aging and health (Pedersen, Steffensson, Berg, Johansson, & McClearn,1999), aging and memory (Della-Maggiore, Sekuler, Grady, Bennett, Sekuler, & McIntosh, 2000), aging and perception (Salthouse, Toth, Daniels, Parks, Pak, Wolbrette, & Hocking, 2000), AIDS and HIV counseling (Nyamathi & Stein, 1997), AIDS risk behaviors (Schröder, Hobfoll, Jackson, & Lavin, 2001;Stein, Nyamathi, & Bentler, 2001), alcohol expectancies (Wood, Read, Palfai, & Stevenson, 2001), alcohol prevention (Taylor, Graham, Cumsille, & Hansen, 2000), alcohol use (Barnes, Murray, Patton, Bentler, & Anderson, 2000;Harford, & Muthén, 2001;Lonczak, Huang, Catalano, Hawkins, Hill, Abbott, Ryan, & Kosterman, 2001;…”
Section: Illustrative Applicationsmentioning
confidence: 99%
“…One of the best ways to learn about this methodology is to study practical applications in your field. Some recent references are the following: ability growth and decline (Raykov, 2000), absenteeism (Geurts, Schaufeli, & Rutte, 1999), academic self concept and achievement (Marsh, Byrne, & Yeung, 1999;Marsh, Hau, & Kong, 2002), acculturation (Gil, Wagner, & Vega, 2000), achievement goals (Elliot & McGregor, 2001), achievement inequality (Carbonaro & Gamoran, 2002), achievement motivation (Barron & Harackiewicz, 2001), achievement tests (Muraishi & Toyoda, 1998), action and coping self-efficacy (Schwarzer, & Renner, 2000), action-control beliefs (Malmberg, Wanner, Sumra, & Little, 2001), ADHD (Rapport, Scanlan, & Denney, 1999), adolescent dating (Wolfe, Scott, Reitzel-Jaffe, Wekerle, Grasley, & Straatman, 2001), affect (Remington, Fabrigar, & Visser, 2000), affect and alcohol problems (McCreary & Sadava, 2000), affirmative action (Iyer, Leach, & Crosby, 2003;Federico & Sidanius, 2002), aging and health (Pedersen, Steffensson, Berg, Johansson, & McClearn,1999), aging and memory (Della-Maggiore, Sekuler, Grady, Bennett, Sekuler, & McIntosh, 2000), aging and perception (Salthouse, Toth, Daniels, Parks, Pak, Wolbrette, & Hocking, 2000), AIDS and HIV counseling (Nyamathi & Stein, 1997), AIDS risk behaviors (Schröder, Hobfoll, Jackson, & Lavin, 2001;Stein, Nyamathi, & Bentler, 2001), alcohol expectancies (Wood, Read, Palfai, & Stevenson, 2001), alcohol prevention (Taylor, Graham, Cumsille, & Hansen, 2000), alcohol use (Barnes, Murray, Patton, Bentler, & Anderson, 2000;Harford, & Muthén, 2001;Lonczak, Huang, Catalano, Hawkins, Hill, Abbott, Ryan, & Kosterman, 2001;…”
Section: Illustrative Applicationsmentioning
confidence: 99%
“…Serpell's (1993) pivotal longitudinal study in neighboring Zambia showed that schoolgoing children were thought to be enterprising, wise, responsible, and assertive. A similar cultural framework about school-going children in Tanzania might be proposed with Swahili concepts (Malmberg, Wanner, & Sumra, 2001): Uweza refers to ability; a child who has a lot of akili is a child with intelligence. And children from urban families, like the ones in this study, have more resources and their parents are more educated; urban school-going children thus have higher expectations for higher education (Malmberg et al, 2001).…”
Section: School Childrenmentioning
confidence: 99%